Psychometric properties of an Arabic translation of the Child–Adolescent Perfectionism Scale – short form (CAPS-9) - Nisma Merdad; Tabassum Rashid; Sarah Faden; Kamel Jebreen; Feten Fekih-Romdhane; Souheil Hallit (International Journal of Adolescence and Youth)
The objective of the study was to examine the psychometric properties of the Arabic version of the nine-item Child–Adolescent Perfectionism Scale (CAPS-9). Five hundred and five adolescents participated in this cross-sectional study (mean age = 16.66; 52.7% females). The two-factor model [self-oriented perfectionism (SOP) and socially prescribed perfectionism (SPP)] indicated a good fit. Internal reliability was adequate for the SPP (ω = 0.82/α = 0.81) and SOP (ω = 0.81/α = 0.80) subscales. Convergent validity was supported by an adequate average variance extracted value. Measurement invariance across gender was supported at the configural, metric, and scalar levels, with no significant difference between males and females. Concurrent validity was demonstrated since higher SPP was significantly associated with higher distress, eustress, physical aggression, anger, and hostility. Higher SOP was significantly associated with higher eustress and anger. The present results demonstrate the usefulness of the Arabic version of the CAPS-9.